The Soft Anomalous Dimension at four loops in the Regge Limit - Niamh Maher, Giulio Falcioni, Einan Gardi, Calum Milloy, Leonardo Vernazza (SciPost Physics Proceedings, 2022)
The soft anomalous dimension governs the infrared divergences of scattering amplitudes in general kinematics to all orders in perturbation theory. By comparing the recent Regge-limit results for $2→2$ scattering (through Next-to-Next-to-Leading Logarithms) in full colour to a general form for the soft anomalous dimension at four loops we derive powerful constraints on its kinematic dependence, opening the way for a bootstrap-based determination.